Introgression of alien genes for leaf rust (Puccinia recondita) resistance into bread wheat (Triticum aestivum) cultivars - TOMAR, S M S; MENON, M K (The Indian Journal of Agricultural Sciences, 2013)
A study Was conducted during 1983-96 to produce backcross lines. Nineteen bread wheat (Triticum aestivum L, emend, Fiori & Paol.) cultivars susceptible to leaf rust (Puccinia recondita Rob, ex Desm, f. sp tritici) were chosen for incorporating resistance genes of alien origin, viz Lr 9, Lr 19, Lr 24 and Lr 28. Six to eight backcrosses were given. The evaluation of these backcross improved lines along with their recurrent parents under natural and artificial epiphytotic conditions revealed that they confer adult plant resistance to leaf rust pathotypes prevailing in the Nilgiri hills. Seedling test against selected Indian leaf rust pathotypes of 19 lines provided an evidence that they carry Lr 24. The backcross derived lines carying Lr 9, Lr 19 and Lr 28 exhibited variable pattern of infection type at seedling stage against leaf rust pathotypcs 77-1 and 77-5 indicating the difference among the type of resistance imparted by these genes. Seedling test against stem rust pathotypes 40 A and 40-1 of backcross lines carrying Lr 24/Sr 24 exhibited resistance to 40A but susceptibility to 40-1, those carrying Lr 19/Sr 25 showed resistance to both pathotypes while those carrying Lr 28 showed susceptibility. The rust reaction taken at different stages of plant growth of backcross lines carrying Lr 19/Sr’ 25 indicated that Sr 25 provides adult plant resistance to the stem rust pathotypes occurring in the Nilgiris. The availability of the above alien genes in the background of adapted wheat cultlvars will enhance the exploitation in wheat breeding in India and elsewhere in agriculture and that they could be blended to constitute multilines.